(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This article seeks to contribute to the dissemination of the history of Brazilian design through the modern furniture developed by designer Karl Heinz Bergmiller, to compose the administrative environments of the Itamaraty Palace, in Brasília, in the 1960s and 1970s. Rescuing its history and memory, dialoguing with interface of design knowledge, education and its relationship with the preservation of Brazilian cultural heritage, aims to promote the democratization of access to movable cultural assets integrated into modernist architecture. Through a restoration project carried out by the Research Center in Modern Furniture of the Federal Institute of Brasília (IFB) Samambaia campus, through a Technical Cooperation Agreement between IFB and the Ministry of Foreign Affairs (MRE) and with the support of the University of Brasília (UnB), research was carried out on documents, drawings, photographs and production methods of the time. To this end, the IFB School of Modern Furniture Restoration Workshop, through a teaching, research and extension action in the thematic area of cultural heritage and recovery of movable cultural assets, recovered part of the Itamaraty Palace collection, signed by Karl Heinz Bergmiller.